Production potential and influence of chemical fertilizers, organic manures and bio-fertilizers on growth, yield and economics of mustard - Khare, Archana; Raghuwanshi, Amit Prakash; Tripathi, Kul Bhushan Mani; Mishra, Archana; Tiwari, Archana; Singh, Noopur (Journal of Postharvest Technology, 2024)
Mustard (Brassica juncea L.), ) is an important oilseed crop in the Indian subcontinent and it provides around27 % So, to elucidate the effect of INM in mustard growth and yield a field experiment was conducted during Rabi season 2018-19 at Agricultural Research Farm in faculty of Agricultural sciences and Allied Industries Rama University, Mandhana, Kanpur (U.P.). The mustard variety cv. Varuna was laid out in a randomized block design with twelve treatment replicated in thrice and treatment details are T1 (Control), T2 ( 100% RDF), T3 (100% RDF + Vermicompost @ 5t ha-1), T4 (100% RDF + Vermicompost @ 5t ha-1 + PSB), T5 (100% RDF + Poultry manure @ 2t ha-1), T6 (100% RDF + Poultry manure @ 2t ha-1 + PSB), T7 (75% RDF), T8 (75% RDF + Vermicompost @ 5t ha-1), T9 (75% RDF + Vermicompost @ 5t ha-1 + PSB), T10 (75% RDF + Poultry manure @ 2t ha-1 ) and T11 (75% RDF + Poultry manure @ 2t ha-1 + PSB).The application of 100% RDF + Poultry manure @ 2t ha-1 + PSB was recorded significantly highest plant growth viz. plant height, dry matter accumulation, primary and secondary branches and leaf area index as well as yield attributes viz., number of siliqua plant-1 (g), number of seed siliquae-1 and test weight as compared to the rest of the treatment.The treatment T6 (100%RDF+Poultry manure @ 2t ha-1 + PSB)was recorded maximum 22.93 qha-1 (grain yield), 52.66 qha-1 (Stover yield) with Rs. 67138.00 ha-1 net return and B: Cratio (2.55) in comparison to rest of the treatment.